Prevalence of solitary thyroid nodule and evaluation of the risk factors associated with occurrence of malignancy in a solitary nodule of thyroid - Kishan, A. Manmadha; Prasad, Kameshwari (International Surgery Journal, 2018)
Background: A solitary nodule may become cosmetically distressing to a patient and occasionally causes pressure symptoms. Less frequently, an autonomously hyper functioning single nodule may cause hyperthyroidism. However, in the greater proportion of patients the major concern relates to the potential of malignancy with in such a nodule. Objective of present study was to study prevalence of solitary thyroid nodule and evaluate the risk factors associated with occurrence of malignancy in a solitary nodule of thyroid. Methods: This is a prospective study of randomly selected patients with clinically palpable, solitary thyroid nodule diagnosed and treated at Prathima Institute of Medical Sciences Karimnagar. Total duration of study was two years, from 2010 October to 2012 September. Results: The prevalence was found to be 19.2% in the present study. Majority were females i.e. 86.7%. It was found that maximum i.e. 36% of the cases belonged to the age group of 21-30 years. Swelling of the thyroid region was present in all cases. 97% of the patients were found to be euthyroid. FNAC showed that majority had follicular neoplasm. Hemi-thyroidectomy was the most common method used in 62 cases. Cytology diagnosis as Follicular neoplasm was the most common indication of surgery in 34 cases. Follicular adenoma was the most common histopathological finding in 43% of the cases. Benign lesion was the most common lesion in both males and females. Papillary cancer was the most common. The sensitivity of FNAC was found to be 94%. Conclusions: FNAC is the gold standard for evaluation of solitary thyroid nodules with an accuracy of 94% in our study. Females are more commonly affected than Males. 11.4% of Solitary Thyroid nodules were malignant. Suspect malignancy at extremes of age. Malignant potential of solitary thyroid nodule after 6th decade is 50%.